The Limits of Heteronormative Sexual Scripting: College Student Development of Individual Sexual Scripts and Descriptions of Lesbian Sexual Behavior - Pham, Janelle M. (Frontiers in Sociology, 2016)
Simon and Gagnon’s sexual script theory identifies multi-tiered influences which shape individual ideas about sexual relationships. The cultural celebration of heterosexuality as the accepted standard dominates major social institutions, and permeates cultural sexual messages. The reception of these heteronormative messages influences the formation of individualized sexual scripts; however, how individuals apply these individualized scripts to understanding the sexual lives of others is little understood. More specifically, what are the effects of heteronormative sexual scripting for imagining a sexual scenario not marked by a male-female partnership? This study asked a sample of heterosexual, bisexual and non-identified college students at a four-year private institution in the northeastern United States to define lesbian sex. Results suggest the influence of culturally heteronormative sexual messages for orienting one’s initial understanding of what sex is, though participants described various levels of acceptance, rejection and/or revision of these messages as they formed their own scripts. However, when asked to define lesbian sex, participants drew from the more rigid heteronormative cultural script to form their definitions. The association of lesbian sex with vaginal penetration by a phallic substitute, such as a dildo, affirmed the overarching influence of the heterosexual, male-centric sexual standard for shaping the individual sexual imaginary.